Effect of changes in salt intake on nocturnal blood pressure dipping and diurnal urinary sodium excretion in normotensive adolescents - Mya Mya, Thwin; Aung, Khaing; Mya Thanda, Sein (2019)
Objective: To determine effect of changes in salt intake on nocturnal dipping of blood pressure and diurnal urinary sodium excretion in normotensive adolescents Methods: Thirty-six normotensive adolescents (age = 15.9 ± 0.9yr) were maintained on high salt intake (supplement of salt by 0.12 g/kg body weight/day in addition to normal diet) for one week followed by one- week washout on a regular diet and then low salt intake (regular meal with low salt and avoid salty food) for another one week. On the last day of each intervention period, 24-h ambulatory blood pressure was measured every 30 minute interval with an automatic device (Spacelab 90207) and urine samples were collected for both daytime and nighttime separately and the urinary concentration of sodium was measured by atomic absorption spectrometer. Results: At the end of one-week high salt intake, 19 subjects (52.8%) were classified as non-dippers (those who had < 10% decrease in MAP from awake to sleep) and 17 subjects (47.2%) were as dippers (those who had ≥ 10% decrease in MAP from awake to sleep). When switched to low salt intake, 13 out of 19 previously non-dippers were shifted to dippers and therefore, 30 subjects (83.3%) became dippers and only 6 (16.7%) were non-dippers. The mean 24-h urinary sodium excretion was 200.8 ± 56.3 mmol/d during high salt intake and 86.2 ± 22.3 mmol/d during salt restriction. A significant nocturnal increase in urinary sodium excretion rate was observed in non-dippers during high salt and low salt intake (p < 0.05). In dippers, a significant nocturnal decrease in urinary sodium excretion rate was observed during low salt intake (p < 0.05) but it was not significant during high salt intake. Nighttime urinary sodium excretion rate of non-dippers was significantly higher than that of dippers during high salt intake (p < 0.05). Conclusion: The present study demonstrated that high dietary salt intake would induce attenuated nocturnal dipping of blood pressure with concomitant changes in enhanced nocturnal natriuresis in normotensive adolescents.